Formação de professores para a educação técnica de nível médio: análise do programa especial de formação pedagógica da UTFPR - Claudino, Jane Carla (2011)
Strong demand for technical professionals to meet the growth of the productive sector of the education system requires teachers trained to work at this level of education so as to adequately prepare professionals to not only work, but active citizens and transform society. This reality is not so new in our country, because from the beginning of last century there were several actions for the development of professional education. However, if over the years policies and technological education sought to expand supply, this expansion has not been accompanied by consistent policies with respect to an initial and continuing training of teachers to work in this mode of education in its various levels. Rather, programs and actions were timely nature that do not have the desired effect, since it was temporary, emergency and not very effective. In this context it is important to define the need for courses, curricula and programs are demanded, and especially where the needs of teachers to work in the Professional and Technical Education (EFA) at its various levels and modalities. Given these circumstances and the current period of expansion of the Federal Network of Professional Education, Science and Technology, this research concerns the politics of teacher training for Technical Education and High School for Professional and Technical Education. It is considered that these methods of teaching not only concern the preparation for a profession, but mostly for the exercise of citizenship by a worker who is a producer of goods, wealth and technology. Likewise, we highlight the important role of teachers for the implementation of a quality education. Starting from these premises, we developed a qualitative research through literature review, documentary analysis and semistructured interviews, the Special Program of Pedagogical Education Federal Technological University of Parana in order to ascertain whether and how the design and methodology used in this program may contribute to the students who undergo this training may become critical educators, efficient and conscious of their social role. Besides the analysis of documents of that Program, Procedure, Notice of Open Class and information site, we conducted semi-structured interviews with students, teachers and the course coordinator. These interviews allowed us to evaluate the views of participants on relevant issues in the context of Education Vocational and Technical High School, as a role and profile of teachers, definitions of technology and technological education, interdisciplinarity, and adequate training of teachers. The paper presents these results and referrals and suggestions for future research.